Functional Brain Networks: Unique Patterns with Hedonic Appetite and Confidence to Resist Eating in Older Adults with Obesity. Issue 12 (1st November 2020) - Burdette, Jonathan H.; Laurienti, Paul J.; Miron, Laura L.; Bahrami, Mohsen; Simpson, Sean L.; Nicklas, Barbara J.; Fanning, Jason; Rejeski, W. Jack
Abstract : Objective: The purpose of this study was to determine whether baseline measures of hedonic hunger—the Power of Food Scale—and self‐control for food consumption—the Weight Efficacy Lifestyle Questionnaire—were associated with network topology within two sets of brain regions (regions of interest [ROIs] 1 and 2) in a group of older adults with obesity. These previously identified brain regions were shown in a different cohort of older adults to be critical for discriminating weight loss success and failure. Methods: Baseline functional magnetic resonance imaging data (resting state and food cue task) were collected in a novel cohort of 67 older adults with obesity (65‐85 years, BMI = 35‐42 kg/m 2 ) participating in an 18‐month randomized clinical trial on weight regain. Results: The Power of Food Scale was most related to ROI 1, which includes the visual cortex and sensorimotor processing areas during only the food cue state. During both the food cue and resting conditions, the Weight Efficacy Lifestyle Questionnaire was associated with ROI 2, which includes areas of the attention network and limbic circuitry. Conclusions: Our findings show critical, distinct links between brain network topology with self‐reported measures that capture hedonic hunger and the confidence that older adults have in resisting the consumption of food because of both intrapersonal and social/environmental cues.